Awareness of parents towards Teething - Bhavneet, K (Bangladesh Journal of Medical Science, 2012)
Objective: The relationship of the first deciduous tooth eruption and the general health of an infant has always been a subject of curiosity. The enigma of teething although historical, continues to pervade contemporary child health care due to many unexplained teething myths. The treatment modalities used in teething have been diverse. The objective of this study was to evaluate the awareness, beliefs and knowledge of parents towards teething symptoms. Materials and method: Hundred parents were randomly selected from two kindergarten schools and were interviewed according to a structured questionnaire. Collected data was analyzed by a statistical software known as SPSS. Results: Results revealed that though parents knew about teething but there was lack of awareness regarding diverse treatment modalities and the teething myths and realities. Conclusions: More educative programs should be initiated to make parents aware of teething myths and realities. DOI: http://dx.doi.org/10.3329/bjms.v11i1.9822 BJMS 2012; 11(1): 40-43